2010
DOI: 10.1007/s00181-010-0428-x
|View full text |Cite
|
Sign up to set email alerts
|

The properties of survey-based inflation expectations in Sweden

Abstract: This paper assesses the properties of survey-based inflation expectations in Sweden. The survey is conducted by Prospera once every quarter and consists of respondents from businesses and labour-market organisations. The paper shows that inflation expectations measured in this survey tend to be biased and inefficient forecasts of future inflation. Results also indicate that long-run inflation expectations are overly adaptive with respect to actual inflation. Finally, evaluations of forecast accuracy show that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…At the one and two-year forecast horizons, both survey-based measures and market-pricing inferred measures of policy-rate expectations are biased and inefficient. These results are perhaps not too surprising given that survey-based forecasts of Swedish inflation and wage-growth have been shown to have similar shortcomings; see Jonsson andÖsterholm (2011, 2012). And despite the frequently cited disadvantages of both types of policy expectations, neither stand out as a clear winner concerning forecast accuracy.…”
Section: Discussionmentioning
confidence: 94%
“…At the one and two-year forecast horizons, both survey-based measures and market-pricing inferred measures of policy-rate expectations are biased and inefficient. These results are perhaps not too surprising given that survey-based forecasts of Swedish inflation and wage-growth have been shown to have similar shortcomings; see Jonsson andÖsterholm (2011, 2012). And despite the frequently cited disadvantages of both types of policy expectations, neither stand out as a clear winner concerning forecast accuracy.…”
Section: Discussionmentioning
confidence: 94%
“…Beklentilerin pozitif yanlılık sergilediği ve etkinlik için ise kesin bir karara varılamadığı ifade edilerek rasyonel beklentiler hipotezinin geçerli olmadığı sonucuna ulaşılmıştır. Jonsson ve Osterholm (2010), çalışmada İsveç için enflasyon beklentilerinin rasyonelliğini incelemişlerdir. 1996-2009 dönemi itibariyle yansızlık ve etkinlik testleri kapsamında beklentilerin rasyonel forma sahip olmadığını tespit etmişlerdir.…”
Section: Li̇teratür Taramasiunclassified
“…Making use of survey expectations of 12 European countries, Ghonghadze and Lux (2012) obtained a superior out-of-sample forecasting performance with a canonical opinion dynamics model than with univariate time series models. Jonsson and Österholm (2012) analysed the inflation expectations formation process in Sweden using survey expectations, obtaining a poor forecasting performance that could be partly attributable to a mismeasurement of expectations. However, Österholm (2014) found that survey-based expectations improved the out-of-sample forecasting performance of GDP growth predictions in Sweden.…”
Section: Introductionmentioning
confidence: 99%